A Comprehensive Review on Topical Treatment Strategies for Tinea Pedis: Formulation Approaches and Clinical Outcomes - Mayuri Pol; Dr. Sunil. K. Mahajan; Rohit Bhaurao Ingle; Dr. Deepak D. Sonawane (Asian Journal of Pharmaceutical Research and Development, 2026)
Tinea pedis, also called athlete’s foot, is among the commonest superficial mycoses, mainly attributed to dermatophytes belonging to the genus Trichophyton. This disease affects a considerable number of people worldwide, mostly those living in hot and humid climates, wearing occlusive shoes, and with low hygienic standards. The condition can occur in different forms, namely interdigital, moccasin, and vesiculobullous forms, presenting symptoms such as pruritus, scaling, erythema, and pain. The identification process involves a clinical assessment alongside laboratory procedures like KOH microscopy, fungal culture, and molecular diagnostics. While topical antifungal medications represent the principal form of treatment due to their targeted nature, low side effects, and enhanced safety profile relative to oral formulations, the traditional antifungal drugs available, like azoles and allylamines, can suffer from several shortcomings. These include skin penetration issues, extended therapy periods, and rising drug resistance. In response to these limitations, numerous improvements have been made concerning the development of novel drug delivery technologies, incorporating nanocarrier systems, hydrogels, in-situ gels, and film-forming systems, among others.However, challenges like recurrence, resistance, and patient non-compliance continue to be a problem. This article presents an extensive discussion about the pathophysiology, diagnosis, and treatment modalities of tinea pedis using topical therapy. Formulation development is also highlighted in this paper, together with recent breakthroughs and future directions for this common skin disease.